PELATIHAN PENYUSUNAN LAPORAN KEUANGAN MENGGUNAKAN APLIKASI ZAHIR DAN STRATEGI PROMOSI MELALUI SOSIAL MEDIA PADA DPD GERAKAN KEWIRAUSAHAAN NASIONAL PROVINSI JAWA TENGAH (GKN JATENG) - Ratnasari, Fina; Handayani, Puspita; Ambarwati, Ambarwati (Fokus ABDIMAS, 2023)
This community service (PKM) is in collaboration with the National Entrepreneurship Movement of Central Java Province. The purpose of this PKM is to provide guidance and an overview of making financial reports through the Zahir system to MSME owners who are members of the Central Java GKN. This PKM activity was held on Monday, October 24 2022 via zoom meet which was attended by twelve participants, namely from Pamulang University attended by a team of accounting lecturers, Fina Ratnasari, S.E., M.Ak., Ambarwati, SE, M.Sc, and Puspita Handayani, S.E., M.Ak. and 9 MSMEs that are members of the Central Java GKN. It is hoped that with virtual (online) mentoring by the implementing lecturer of the PKM Accounting Study Program, Faculty of Economics, University of Pamulang, Tangsel regarding making financial reports using the Zahir application and marketing products using social media in businesses that are members of the Central Java GKN, it will increase the sustainability of these MSMEs. This PKM is expected to benefit various parties including MSME owners, students and academics.Keywords: Sustainability, UMKM, GKN Jateng,